2006
DOI: 10.1540/jsmr.42.9
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between the responses of electrogastrograms, heart rate and respiratory rate to the stress of the mirror drawing test in human subjects

Abstract: Original C o r r e l a t i o n s b e t w e e n t h e r e s p o n s e s o felectrogastrograms, heart rate and respiratory rate to the stress of the mirror drawing test in human subjects AbstractAn electrogastrogram (EGG) recorded on the skin is believed to reflect the electrical activity of the gastrointestinal tract. In this study, linear correlations were calculated for the EGG spectral frequencies and the power ratios, changes in heart and respiratory rate before and during mirror drawing test (MDT) stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
(39 reference statements)
2
17
0
Order By: Relevance
“…In fact, stress induces dual excitatory and inhibitory effects on gastrointestinal activity Enck, 1991: Musial andEnck, 1993). We have previously reported the effects of acute stress of MDT on the gastric and colonic facilitation and inhibition with EGG (Homma, 2005(Homma, , 2006(Homma, , 2009.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, stress induces dual excitatory and inhibitory effects on gastrointestinal activity Enck, 1991: Musial andEnck, 1993). We have previously reported the effects of acute stress of MDT on the gastric and colonic facilitation and inhibition with EGG (Homma, 2005(Homma, , 2006(Homma, , 2009.…”
Section: Discussionmentioning
confidence: 99%
“…To make topographic EGG maps, the electrode positions were represented by two-dimensional standard coordinates, Xi and Yi, and a spectral peak at a certain electrode position was expressed as Zi = (Xi,Yi) (Homma, 1997: Homma et al, 1999: Homma, 2006. Thereafter, the contour map program (Shiono et al, 1988) was applied and EGG maps were drawn for the power content ratio (Homma, 1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be mentioned that the differences in values in Fig. 7 may be subtle, because the value of LF/HF may range from 0 to 7 [12].…”
Section: Results Of Measured Biological Signalsmentioning
confidence: 99%
“…In studies of response to stress using the mirror drawing test (MDT), in which the subject traces along the edge of a metal star reflected in a mirror, it has been shown that resting scores associated with depression had a negative linear correlation with respect to EGG frequency, while the anxiety scores demonstrated a positive linear relation with respect to EGG area power ratio (Homma, 2006). This research also showed that acute stress had a correlated effect on the GEA of visceral smooth muscle evidenced by EGG.…”
Section: Triggering Sourcementioning
confidence: 99%